1998
DOI: 10.3109/10253899809167290
|View full text |Cite
|
Sign up to set email alerts
|

Increased Heat Shock Protein Expression after Stress in Japanese Quail

Abstract: Heat shock proteins (HSPs) have been shown to provide information on the biological impact of environmental stress to organisms, yet none have investigated the HSP response to stress in birds. Japanese quail were exposed to seven different stressors (mild restraint, loud noise, inescapable irritation, cold temperature, isolation in darkness, and two stressful social situations) and expression of HSP30, 60, 70, and 90 in heart, liver, lung, kidney and gonads was examined. Tonic Immobility (TI) tests were also c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1
3

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 25 publications
1
11
1
3
Order By: Relevance
“…Little is known about the effects of noise on Hsp expression. Wu et al (Wu et al, 2001) showed that Hsp70 expression increased after exposure to a stressful noise in humans, and Hoekstra et al (Hoekstra et al, 1998) reported that the expression of Hsp70 (but not Hsp30, Hsp60 or Hsp90) is increased in birds after exposure to a loud noise. We have also recently detected increased Hsp70 expression in the fish Chromis chromis after exposure to sounds similar to those resulting from human activities (M.V., M.C., D. Arizza, G. Calandra, G.B., D.P., V. Ferrantelli, C. Bracciali and G. Sarà, unpublished).…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about the effects of noise on Hsp expression. Wu et al (Wu et al, 2001) showed that Hsp70 expression increased after exposure to a stressful noise in humans, and Hoekstra et al (Hoekstra et al, 1998) reported that the expression of Hsp70 (but not Hsp30, Hsp60 or Hsp90) is increased in birds after exposure to a loud noise. We have also recently detected increased Hsp70 expression in the fish Chromis chromis after exposure to sounds similar to those resulting from human activities (M.V., M.C., D. Arizza, G. Calandra, G.B., D.P., V. Ferrantelli, C. Bracciali and G. Sarà, unpublished).…”
Section: Discussionmentioning
confidence: 99%
“…In crustaceans, the expression of Hsp70 serves as a good bioindicator of stressful conditions, including pesticide exposure and heat stress (Snyder and Mulder, 2001;Liberge and Barthélémy, 2007;). Only a few studies have examined the effects of noise on Hsp expression (Hoekstra et al, 1998;Wu et al, 2001;Celi et al, 2013). Recently, increased Hsp70 expression levels were detected in Chromis chromis after exposure to sounds similar to those resulting from human activities (Celi et al, unpublished).…”
Section: Behavioural and Haemato-immunological Responses To Noise Polmentioning
confidence: 99%
“…Little is known about the effects of noise on Hsp expression. Wu et al (2001) showed that Hsp70 expression increased after exposure to a stressful noise in humans, and Hoekstra et al (1998) reported that the expression of Hsp70 (but not Hsp30, Hsp60 or Hsp90) is increased in birds after exposure to a loud noise.…”
Section: Introductionmentioning
confidence: 99%
“…It interacts with newly synthesized glycoproteins and putative chaperones such as calnexin and calreticulin. Heat shock cognate 71 kDa protein is a cognate form of HSP70, and one of the HSP70 family proteins, which helps to fold many proteins (Hoekstra et al, 1998;Laios et al, 1997). Hsp70assisted folding involves repeated cycles of substrate binding and release.…”
Section: Proteomic Analysis By 2-d Pagementioning
confidence: 99%